Customary Law Ascertained Volume 2 : The Customary Law of the Bakgalagari, Batswana and Damara Communities of Namibia - Gairiseb, Alexander; Hinz, Manfred O., 1936- (Book collections on Project MUSE., 2014)
Customary Law Ascertained Volume 2 is the second of a three volume series in which traditional authorities in Namibia present the customary laws of their communities. It contains the laws of the Bakgalagari, the Batswana ba Namibia and the Damara communities. The recognised traditional authorities in Namibia are expected to ascertain the customary law applicable in their respective communities and to note the most important aspects of the laws in written form. The Ministry of Regional and Local Government, Housing and Rural Development, and the Council of Traditional Leaders therefore initiated the ascertainment of customary law. The ascertainment project is housed in the Human Rights and Documentation Centre of the University of Namibia. The former Dean of the Faculty of Law of the University of Namibia, Professor Manfred O. Hinz, has directed the project since its inception.